Molusco contagioso del párpado: manifestación cutánea de inmunosupresión - Camilo Andrés Morales-Cardona (Asociación Colombiana de Infectología, 2021)
Molluscum contagiosum is a cutaneous viral infection, usually benign and self-limited, caused by the molluscum contagiosum virus, of the genus Molluscipoxvirus. It is more common in pediatric population, sexually active young people and immunosuppressed patients. Clinical presentation is characterized by umbilicated white to flesh-colored or pearly papules, which rapidly spread and can affect any muco-cutaneous membrane. Although the eyelid presentation is atypical, we herein present two young, immunosuppressed patients, with diagnosis of palpebral molluscum contagiosum, in which the initial clinical diagnosis was wrong. We emphasize the importance in making a timely diagnosis of papular lesions localized on the eyelids and the correlation of these lesions as a cutaneous manifestation of immunosuppression.